The bottleneck may be the solution, not the problem. (2016) - Lotem, Arnon; Kolodny, Oren; Halpern, Joseph Y.; Onnis, Luca; Edelman, Shimon
Abstract: As a highly consequential biological trait, a memory "bottleneck" cannot escape selection pressures. It must therefore co-evolve with other cognitive mechanisms rather than act as an independent constraint. Recent theory and an implemented model of language acquisition suggest that a limit on working memory may evolve to help learning. Furthermore, it need not hamper the use of language for communication.